Interactions of Giardia sp. with the intestinal barrier: Epithelium, mucus, and microbiota. Issue 1 (2nd January 2017) - Allain, Thibault; Amat, Christina B.; Motta, Jean-Paul; Manko, Anna; Buret, André G.
ABSTRACT: Understanding how intestinal enteropathogens cause acute and chronic alterations has direct animal and human health perspectives. Significant advances have been made on this field by studies focusing on the dynamic crosstalk between the intestinal protozoan parasite model Giardia duodenalis and the host intestinal mucosa. The concept of intestinal barrier function is of the highest importance in the context of many gastrointestinal diseases such as infectious enteritis, inflammatory bowel disease, and post-infectious gastrointestinal disorders. This crucial function relies on 3 biotic and abiotic components, first the commensal microbiota organized as a biofilm, then an overlaying mucus layer, and finally the tightly structured intestinal epithelium. Herein we review multiple strategies used by Giardia parasite to circumvent these 3 components. We will summarize what is known and discuss preliminary observations suggesting how such enteropathogen directly and/ or indirectly impairs commensal microbiota biofilm architecture, disrupts mucus layer and damages host epithelium physiology and survival.